Are inequalities in height narrowing? Comparing effects of social class on height in two generations. Issue 11 (21st October 2004) - Li, L; Manor, O; Power, C
Abstract : Objective: To determine whether social inequalities in height change across generations. Methods: The target population was from the 1958 British birth cohort, all born 3rd–9th March 1958, followed to 1991, and the offspring of one third of this population. Main outcomes were height measured at 7, 11, 16, and 33 years (cohort members) and once at 4–18 years (offspring). Multilevel models applied to associations of social class of origin with (a) child-to-adult growth trajectory (cohort members), (b) height (offspring), and (c) generational height increment. Results: Height inequalities were observed among cohort members, with differences >2.0 cm at all ages between classes I and II, and IV and V. By adulthood, the difference in mean height had declined significantly in boys and slightly in girls. A secular trend was seen between the two generations. While male offspring had a similar mean height to their fathers in classes I and II, boys in classes IV and V gained 2.1 cm (p<0.001). Height gains of female offspring were evident in all classes, with a greater gain in classes IV and V (non-significant). The social class effect on height was weaker among offspring, with a difference between classes I and II, and IV and V of less than 1 cm. Conclusions: Social inequalities in height observed among the cohort weakened substantially in the next generation due to a greater height gain among offspring from manual classes. Inequalities in childhood height have narrowed between the two generations in this study.